Spectrum shortage and merger by any other name in South Africa - Bronwyn E. Howell; Petrus H. Potgieter (International Telecommunications Society (ITS), 2021)
Radio spectrum is a key input for mobile operators and the structure of the industry is strongly related to and influenced by the ownership of spectrum licenses. Spectrum is usually allocated for a limited duration and may or may not be tradable which further complicates the interaction between spectrum ownership and the retail market for mobile services. The adoption of a new constitutional system in 1996 in South Africa created the opportunity for importing a fresh set of recommendeded institutions and policies for telecommunications. This eventually included an independent telecommunications regulator (ICASA), the budget for which nevertheless comes form the responsible Minister. ICASA announced an auction of spectrum in the 2.6 GHz and 3.5 GHz bands in May 2010 and issued a tender for the design of the auction, but this was postponed several times and finally abandoned (Song, 2011). The same thing happened again in 2016 (Paelo & Robb, 2020). Late in 2020, the regulator again announced an auction, due to take place during 2021 but by the beginning of the year, two of the four national operators had already announced that they would go to court to stop the auction. A shortage of spectrum (or, inefficient assignment of it) is blamed for South Africa's relatively slow LTE speeds, among other things. The response of operators has been to innovate using roaming and network sharing agreements. By historical accidents, the country has two wireless networks in addition to the four licences mobile operators. The paper looks at how the de facto industry structure has been determined by spectrum holdings and sharing arrangements and asks how spectrum management could be improved. We observe that although the number of mobile operators has effectively aeen reduced to 3 (a number which would raise concern in some circles) there exist a variety of arrangements between the 3 and also other spectrum and network operator. The smallest of the 3 mobile operators is still not able to offer a nationwide mobile service without a roaming agreement but at the same time the two larger operators depend critically on spectrum and roaming agreements themselves, mainly with the two physical data network operators that function as wholesale providers.
Keywords: 330; Spectrum auction; network sharing; South Africa; ICASA